Challenges at performing minor oral Surgery on pediatric patients from the perspective of the Pediatric Dentist, General Dentist and Oral and Maxillofacial Surgeon (Research, Society and Development, 2023)
Objetivo: Objective: To understand the challenges in managing pediatric patients when performing oral surgery from the perspective of the general dentist, the oral and maxillofacial surgeon and the pediatric dentist. Methodology: There was carried out a survey using a questionnaire developed for this purpose. The sample consisted of dentists with degrees in Dentistry duly registered at the Pernambuco Regional Dental Council and who worked as general practitioners, pediatric dentists, or oral and maxillofacial surgeons. The research has been in accordance with the postulates of the Declaration of Helsinki and the standards for research with human beings recommended by the National Health Council through resolution no. 466/12 and was approved by the Research Ethics Committee. Results: The final sample consisted of 231 dentists. Of the 80 participating pediatric dentists, only 8.7% declared that they had no difficulties in providing care, and 10% declared that they had difficulties communicating with the patient, despite their expertise. Of the 72 general practitioners, 29.1% agreed that their biggest difficulty was gaining the trust of the child patient. Of the 79 oral and maxillofacial surgeons, 44.3% identified controlling the patient's fear as the greatest difficulty, while only 6.3% said they had no difficulties in providing care to child patients. Conclusion: It is worth highlighting that new research addressing the sociodemographic profile and current trends of practicing dental surgeons must be carried out, in addition to work that investigates complications and accidents related to the non-applicability of behavioral management techniques for child patients, since the literature presents few scientific articles with updated data.